Lung Clearance Index and Quantitative Computed Tomography of Post-Infectious Bronchiolitis Obliterans in Infants. Issue 1 (December 2017) - Kim, Yoon; Shin, Hyun; Sol, In; Kim, Soo; Kim, Jong; Yoon, Haesung; Kim, Kyung; Kim, Myung-Joon; Lee, Mi-Jung; Sohn, Myung
Abstract Post-infectious bronchiolitis obliterans (BO) could be diagnosed via spirometry and chest computed tomography (CT); however, these tests are limited in infants. We aimed to evaluate the utility of lung clearance index (LCI) and air-trapping lung volume from chest CT in infants. This prospective study included 20 infants (mean age, 10.9 ± 6.3 months) diagnosed with post-infectious BO between 2009 and 2016. All subjects underwent multiple breath washout tests. For quantitative analysis of chest CT, the mean lung area attenuation value was used as an individual cutoff to determine the air-trapping lung volume. The mean cutoff lung attenuation value was −659 Hounsfield units, the mean total lung volume was 265 ml, and the mean air-trapping lung volume percentage was 22.9%. Functional residual capacity correlated with total lung volume and normal attenuation lung volume (p  < 0.02). LCI (p  < 0.02) and moment ratio (MR) 1 (p  < 0.05) correlated with the air-trapping lung volume percentage. The concordance indices of LCI (0.659, p  = 0.025) and MR1 (0.642, p  = 0.046) were significantly correlated with the air-trapping lung volume percentage from CT. LCI and quantitative air-trapping lung volume from chest CT are feasible, complimentary tools for assessing infants with post-infectious BO.